Pijat Tui Na Meningkatkan Berat Badan Bayi Usia 6-12 Bulan - Ximenes, Marquita Da Silva; Retno Setyo Iswati; Desta Ayu Cahya Rosyida (WOMB Midwifery Journal, 2024)
Infancy is an important period for growth and development. One of the factors causing problems in baby's weight is a lack of nutrient intake, which is often caused by babies having difficulty eating and choosing food. Tui Na massage is an alternative way to increase weight. The method in this research uses a pre-experimental research design type one group pretest-posttest. The sampling technique used purposive sampling technique. The sample used was 30 babies. Data analysis consists of univariate analysis, which is carried out based on the type of data, both categorical and numerical, and bivariate analysis using the t-test. The results of this study showed that before the Tui Na massage, all 30 babies aged 6-12 months had a fixed weight, that is, the weight after being given the Tui Na massage was that most of the babies gained weight, totaling 27 babies. This shows that there is an effect of Tui Na massage on body weight in babies aged 6-12 months with a p-value of 0.001.